Stimulating Commercial Drones with Open Spectrum Paradigm - Kim, Se Ho; Oh, Sang Hoo; Lee, Bong Gyou (International Journal of Management and Sustainability, 2016)
As the number of services that use spectrum such as IoT and commercial drones are increasing rapidly every year, it has become very important to efficiently allocate the spectrum resources. Advanced countries are shifting towards open spectrum system which provides the suitable environment for using radio wave and pursue new technological service innovation. Global companies such as Amazon, DHL, and Google are already investing a lot of resources into the commercial drone technology and made significant contributions. Korea’s commercial drone industry, on the other hand, had limited growth because commercial drones are strictly regulated. In this respect, the purpose of this paper is to derive a policy measure for open spectrum to foster the Korean commercial drone industry. The research was conducted as follows: (i) Literature review of open spectrum and commercial drone industry and (ii) Expert interview on key issues. Following implications have been drawn from case studies in other countries and the expert interview: (i) Establishing data-based open spectrum management system, (ii) Designing a plan to develop new service using spectrum in middle and long term, (iii) Selecting spectrum band width exclusive for open spectrum and drone for international compatibility (iv) The need for a unified agency which can manage and regulate drone industry. These results imply that in order to foster the commercial drone industry, it needs a collaboration with the field of spectrum, and an international standard. The contribution of this study is to provide a strategic guideline for the countries that are in the early stage of developing commercial drone industry, and establish policy and legal guidelines to help foster commercial drone industry.